DNA Barcoding of Endophytic Bacteria from The Stems of Tissue Piper crocatum and Activity Anti-Bacterial Properties - Lalu Wira Zain Amrullah; Lalu Zulkifli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Secondary metabolites from herbal are commonly used to treat disease due to infection from pathogenic bacteria, endophytic bacteria is shortcut to collect secondary metabolites more effective than extracting direct from the plant. This research aims to obtain endophytic bacterial isolates from the stems of the red betel plant which can be used as an inhibitor for the growth of pathogenic bacteria. The method of this research is exploratory descriptive experiment based research. The stages of this research consist of few techniques which are isolation of endophytic, antibacterial examination, morphological, physiological, and biochemical observation, DNA bacterial extraction, gel electrophoresis. To analyse DNA Barcoding using 16S rRNA gen, BLAST and MEGA 10. The results of the antibacterial activity of the isolates showed by clear zone formation against pathogenic bacteria such as E. coli, K. pneumoniae and S. aureus. Endophytic bacterial that successfully isolated are labelled (BSM1, BSM2, BSM3 and BSM4). Based on of the Gel electrophoresis shows that four endophytic bacterial isolates are positive by appearance of bands in 1324bp. Based on the results of the phylogenetic tree it can be concluded that BSM1 is closely related to Bacillus cereus JL with a genetic distance of 0.007, while the genetic distance of BSM2 was 0.012, BSM3 0.006 and BSM4 0.003, all three were closely related to Bacillus pumilus AUEC29.